Evaluasi Perdebatan James Dunn dan Simon Gathercole di Seputar Isu New Perspective - Chandra Gunawan (STT Amanat Agung, 2009)
New Perspective sebagai pandangan baru yang mengkritik teologi gereja reformasi telah menjadi demikian kuat. Seyoon Kim mengomentari New Perspective demikian: “Since Reformation, I think no school of thought, not even the Bultmannian School, has exerted a greater influence upon Pauline scholarship than the school of the New Perspective.”